The Portrait of Wellness Tourism during the COVID-19 Pandemic in Indonesia. A Case Study of Health Protocol Implementation at Green Kubu Café Bali - WIRAWAN, Putu Eka; WIDHIARINI, Ni Made Ayu Natih; SUDIARTA, I Nyoman; YANI, Ni Wayan Mega Sari Apri; NURUDDIN, Nuruddin (Journal of Environmental Management and Tourism; Vol 14 No 8 (2023): JEMT, Volume XIV, Issue 8(72), Winter 2023, 2023)
Wellness tourism themed is currently a new trend because it aims to maintain the physical, mental, emotional, social, environmental, and spiritual aspects of tourists. This study is qualitative-descriptive research with data collection methods in the form of interviews, observations, and documentation. This study aims to look at the implementation of CHSE-based health protocols on tourist visits at Green Kubu Café, Tegallalang District, Gianyar Regency during the COVID-19 pandemic. The results of this study indicate that the implementation of the CHSE-based health protocol on tourist visits at Green Kubu Café has been going well, although it has not yet reached perfection. The satisfaction and loyalty of tourists who visit Green Kubu Café due to the implementation of the CHSE-based health protocol is also not meaningful or has no major influence, so the purpose of implementing the CHSE certification as stated by the Ministry of Tourism and Creative Economy is to provide guarantees to tourists for cleanliness, health, safety, and safety environmental sustainability has not been maximized.